ANALYSIS OF THE ISLAMIC HISTORY ENCYCLOPEDIA AS A SUPPLEMENTARY BOOK FOR THE ISLAMIC CULTURAL HISTORY - Maya, Rahendra; Samsuddin; Alfarisi, Muhammad Fadilah; Aisyah; Masuwd, Mowafg Abrahem (INTIHA: Islamic Education Journal, 2025)
Students enrolled in the Islamic Religious Education (PAI) Study Program are trained to become professional teachers capable of teaching all branches of PAI subjects in schools and madrasahs, including Islamic Cultural History (SKI). The SKI Learning System in Madrasahs course aims to equip students with pedagogical competencies in teaching SKI. However, the limited availability of adequate teaching materials and learning resources poses a challenge in this learning process. This study aims to analyze the feasibility of the Encyclopedia of Islamic History, compiled by the Research and Islamic Studies Team of Egypt, as a supplementary book for the Islamic Cultural History textbook published by the Indonesian Ministry of Religious Affairs in 2020. This research employs a qualitative method with a library research approach. Data collection techniques include literature review and documentation, while data analysis is conducted using a descriptive-interpretative method. The findings indicate that the Encyclopedia of Islamic History is suitable as a supplementary book for SKI learning. This book explores Islamic culture from a historical perspective and shares similarities in content with 15 out of 20 chapters in the Ministry of Religious Affairs textbook. Therefore, it serves as an effective reference for SKI teachers and prospective PAI educators, including fourth-semester students at STAI Al-Hidayah Bogor.